A SEDIMENT CARBON STOCK OF WEST KALIMANTAN MANGROVE FOREST - Nuraya, Tia; Koropitan, Alan F.; Wahyudi, A'an J. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2019)
The present study aims to investigate the influence of oceanographic factor and riverine input on  mangrove ecosystem and their ability in  absorbing carbon. The location of the study was conducted in two different locations in West Kalimantan, which are (1) Mempawah and (2) Bakau Besar. The sediment sampling was carried out using PVC pipes in the middle of the transect point and taken within ± 20 cm depth. After laboratory pre-treatment, we analyzed the carbon content using CHN Analyzer. The results showed that station 3 of Mempawah and station 2 of Bakau Besar have a high organic carbon content, i.e., 6.46 ± 0.23 ton C/ha and 14.93 ± 1.43 ton C/ha, respectively. We also found that input organic carbon in the river (location 2) and canal (location 1) were higher at high tide than low tide. Besides that, we also found that the sediment type at station 3 of Mempawah is categorized as silt (75%) and fine sand (± 0.24%). Whereas at station 2 of Bakau Besar, the sediment contains silt (68%) and fine sand (± 2%). In addition, those two stations have a total mangrove density up to 13519 individuals/ha and 9928 individuals/ha, respectively. According to this findings, we suggest that high organic carbon is influenced not only by high biomass density but also by the oceanographic factor that affects load of organic carbon in river and canal, and the difference of sediment types that are influenced by breaking wave height at the study site. Keywords: mangrove ecosystem, organic carbon, oceanographic factor, West Kalimantan